Using Real Estate Websites to Learn Measures of Central Tendency - Zito, Rena (TRAILS: Teaching Resources and Innovations Library for Sociology, 2014)
This assignment, which requires students to use real-world data on home prices to generate and analyze measures of central tendency, can be adapted as an in-class assignment or homework assignment for undergraduate research methods or social statistics courses. Unlike many assignments on this subject, which use GSS or Census data, this assignment requires students to use online sources to gather their own data about their local community, enter it into SPSS on their own, and calculate—both by hand and using SPSS—measures that they can use to think deeply about shapes of distributions and how levels of measurement and research questions dictate appropriate measures of central tendency. Students enjoy using the real estate listings because they provide a visual representation of the data. The assignment is most effective when begun and followed up with a class discussion of why social scientists might be interested in studying home prices, including the social consequences of the distribution of home prices for the community.